Política lingüística, bilingüismo y rol del maestro de inglés: una revisión desde el entorno global al contexto colombiano - Morales Llano, Reinelio (Colombian Applied Linguistics Journal, 2022)
A language policy is a means by which the structure, function, use or acquisition of a language can be impacted. In addition, it is composed of a set of implicit and explicit elements, such as the practices of the language, linguistic beliefs and ideologies, and official documents or regulations. Given that, this is a topic of growing interest to the academic and scientific community, this article seeks to review the literature on language policy in two steps. First, a search in the Scopus database, to identify trends and theoretical perspectives, through the use of bibliometric tools. Then, a choice of articles and doctoral theses, to be analyzed and identify the theoretical and methodological approach of the studies in the international, Latin American and Colombian context, in relation to the search fild. The findings suggest four theoretical perspectives on language policy: structural, linguistic imperialism, sociocultural and multilayer. Furthermore, qualitative research is currently being developed with different methodological approaches, such as textual analysis, critical discourse analysis, interpretive approach and action research. In Colombia there is a clear trend towards studies based on the theoretical perspectives of linguistic imperialism and sociocultural approach, with methodological approaches based on critical discourse analysis and interpretive analysis.